Kinetics study the decomposition of the cellulose into cellulose nanocrystals by hydrothermal with hydrochloric acid catalyst (International Journal of Plant Biology, 2019)
The aim of this study was to hydrolyzed cellulose nanocrystals as cellulose-based biomass residues from oil palm by using hydrochloric acid under hydrothermal conditions. The characterization of cellulose nanocrystals was determined by FT-IR spectroscopy and X- ray diffraction. The infrared spectroscopy showed there has been a removal of lignin and hemicellulose in the spectrum. Crystallinity which reaches 78.59% was obtained by hydrolysis using hydrochloric acid catalyst 3 mol/L with a reaction time of 1 hour. Based on the graph of -ln CA/CA0 vs. time obtained that Cellulose nanocrystals forming reaction is of first order. The reaction rate constants to the formation of glucose (k2) is greater than the reaction rate constant to the formation of Cellulose nanocrystals (k1), which indicates that the phase of slow reaction is the reaction of the most influential on the overall reaction rate, the reaction of the formation of Cellulose nanocrystals.